Respuestas

2013-04-13T19:33:50+02:00

(cot(2x)+1)(1-cos(2x))=1

(cos(2x)/sen(2x)+1)(1-cos(2x))=1

cos(2x)/sen(2x)-cos(2x)cos(2x)/sen(2x)+1-cos(2x)=1

(cos(2x)-(cos(2x))^2)/sen(2x)=cos(2x)

(cos(2x)-(cos(2x))^2)=cos(2x)sen(2x)

cos(2x)(1-cos(2x))=cos(2x)sen(2x)

1-cos(2x)=sen(2x)

1-((cosx)^2-(senx)^2=2senxcosx

1-(cosx)^2+(sen)^2=2senxcosx

1-(1-(senx)^2)+(senx)^2=2senxcosx

1-1+(senx)^2+(senx)^2=2senxcosx

2(senx)^2=2senxcosx

senx=cosx

senx/cosx=1

tanx=1

x=arctan1

x=45º

o en radianes

x=pi/4 rad

 

2013-04-13T22:20:33+02:00